Level of Readiness for Implementation of the Independent Curriculum in Senior High Schools in Depok City, West Java - Dasmo; Indica Yona Okyranida; Andry Fitrian; Neng Nenden Mulyaningsih; Fita Widiyatun; Irnin Agustina Dwi Astuti (Postgraduate, University of Mataram, 2023)
The Independent Curriculum is a curriculum with diverse intra-curricular learning where the content will be optimized so that students have enough time to explore concepts and strengthen competencies. The purpose of this study was to identify and obtain information about the level of readiness of education units in Depok City in implementing the independent curriculum. The research method used is the descriptive qualitative method, which describes the subject the situation, and data obtained during observations and questions so that it becomes useful information and is easily understood by readers. The results of this study indicate that the level of readiness for implementing an independent curriculum in schools in high school education units in Depok City, West Java, is still not optimal. Two of the three schools have not implemented an independent curriculum, although the school has received socialization and understanding related to the independent curriculum. The key to the success of implementing an independent curriculum is good collaboration between school principals and teachers. In addition, the principal as a leader must be able to change the mindset of the Human Resources in the school to want to make changes so that the independent curriculum can be applied. Likewise, in the project of strengthening the profile of Pancasila students, it is still limited and has not led to a local culture-based learning model